1959
DOI: 10.1152/ajplegacy.1959.196.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Increase in histidine decarboxylase activity of rat skin following treatment with compound 48/80

Abstract: Repeated injections of rats with compound 48/80, a histamine liberator, results in a marked increase in histidine decarboxylase activity of the skin. The increase is roughly proportional to the duration of treatment. This eliminates activation of pre-existing histidine decarboxylase as a probable mechanism. The increase can be demonstrated in intact rats; therefore, rat skin histidine decarboxylase is an adaptive enzyme. It seems probable that 48/80 treatment leads to the production of new, resistant mast cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

1960
1960
2007
2007

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(20 citation statements)
references
References 0 publications
0
19
1
Order By: Relevance
“…The escape from inhibition with semicarbazide alone and the rebound in histamine formation on discontinuing effective inhibition could be explained by the assumption that a reduction in tissue histamine content adaptively elevates the HFC. It has in fact been demonstrated that depletion of rat skin histamine by 48/80 or polymyxin B concomitantly activates skin histidine decarboxylase (Schayer, Rothschild & Bizoni, 1959;Schayer & Ganley, 1959). These circumstances prompted the following experiment.…”
Section: Experiments In Vivomentioning
confidence: 99%
“…The escape from inhibition with semicarbazide alone and the rebound in histamine formation on discontinuing effective inhibition could be explained by the assumption that a reduction in tissue histamine content adaptively elevates the HFC. It has in fact been demonstrated that depletion of rat skin histamine by 48/80 or polymyxin B concomitantly activates skin histidine decarboxylase (Schayer, Rothschild & Bizoni, 1959;Schayer & Ganley, 1959). These circumstances prompted the following experiment.…”
Section: Experiments In Vivomentioning
confidence: 99%
“…On the other hand, Vitamin B6 deficiency states reduced the activity of apocysteine sulfinate de carboxylase [Hope, 1955] and threonine dehydrase [Bergeret et al, 1955]. In addition, the activity of L-aromatic amino acid decarbo xylase was inhibited by using 5-hydroxytryptophan fBuxton and , 1956;Weissbach et al, 1957], dopa [ West, 1953 andSourkes et al, 1960] and histidine [Schayer et al, 1959] as substrates. The addition of PLP restores the activity of the enzyme in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…that histidine decarboxylase is adaptive in nature (Schayer, Rothschild & Bizony, 1959). Attempts to recognize the significance of the elevation of HFC found in physiological and pathological circumstances have followed two currents of thought.…”
Section: Discussionmentioning
confidence: 99%